A retrospective study on head and neck malignancies in a tertiary care hospital in Telangana region - Deva Kumar, K. Samson; Bhushan, Ivaturi Phani; ., Novshaba; Annam, Chandra Shekhar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Globally head and neck cancers constitute amongst 10 most common cancers. In Asia especially in India, global head and neck cancers account to 57.5%.However the true incidence of head and neck cancers in India is hidden suggesting it as ‘tip of iceberg’. India is regarded as having the greatest risk of cancer burden, the reason being population overgrowth. India being the country of diversity, varied cultures and traditions, the demographic characteristic of these cancers also vary in different individuals. Methods: All patients diagnosed with head and neck malignancy after histological confirmation between August 2014 and July 2018 were selected from hospital records. Data regarding age, gender, risk factors, socio economic status, clinical features, staging were taken and statistical analysis was done. Results: A total of 269 cases were collected out of which, 77% of all malignances in males and 23% in females. Squamous cell carcinoma was the most common histological type (94%). Maximum Incidence of HNC (51.6%) was in 40-60 yrs of age. Tobacco was most prevalent risk factor: 58.36% patients present at early stage, 41.63% present at late stage. Conclusions: Oral cancers were most common among all. There is male predominance. Tobacco is the most common modifiable risk factor and most patients presenting at an early stage.